STRATEGI MEDIA RELATIONS DINAS PARIWISATA KABUPATEN ACEH TENGAH UNTUK MEMPROMOSIKAN DESTINASI WISATA - Masriadi; Hasan, Kamaruddin; Cut Adyna , Cut Adyna; Bahri, Halida (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2022)
Media relations in Central Aceh between the Tourism Office and journalists are a central point for increasing the promotion of tourism destinations in 2022 in Central Aceh Aceh Province. The method used in this research is descriptive qualitative. As a tourist area, information is important, one of which is delivered through social media in the form of online, audio/video, and printed information. Therefore, a strategy is needed for approaching relations with the mass media, such as journalists, media entrepreneurs, professional associations of journalists, and associations of media entrepreneurs. In the study of media relations, at least some of the commonly used strategies are known: Press Tours, Media Gatherings, Press releases, Press conferences, Press Receptions, Press Relations, and Media Events. The last part is the evaluation of the practice of media relations strategy. Evaluations aim to analyze whether the strategy used is applicable and followed by the increase in tourist numbers. On the other hand, to reveal if tourists receive information from the mass media or social media, which has been growing rapidly recently in the country. The presence of digital technology helps facilitate official relations with media actors. The presence of various image, text, and video-sending applications makes this relationship should be easier. As a result, the target of bringing in more and more tourists was achieved. In this context, the Central Aceh Tourism Office has used a media relations strategy, but it has not been maximized due to the limited budget available in the 2022 Central Aceh Regional Budget.